2020
DOI: 10.1002/hbm.24993
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of the flash‐induced bouncing effect

Abstract: Two identical visual disks moving toward each other on a two‐dimensional (2D) display are more likely to be perceived as “streaming through” than “bouncing off” each other after their coincidence. However, either a brief auditory tone or visual flash presented at the coincident moment of the disks can strikingly increase the incidence of the bouncing percept. Despite the neural substrates underlying the sound‐induced bouncing effect have been widely investigated, little is known about the neural mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(112 reference statements)
1
0
0
Order By: Relevance
“…Evidence suggested that P2 might be associated with reactivation of the occipital cortex, due to top-down re-entrant feedback from higher-level visual areas back to the early visual cortex. 53 , 54 Consistent with these studies, our study further suggested that 30-degree defects recruited a top-down modulation to re-activate the residual information inputs to enhance visual representations. Thus, visual attention might enhance visual representations via top-down feedback mechanisms, especially in high-level defects with limited visual inputs.…”
Section: Discussionsupporting
confidence: 86%
“…Evidence suggested that P2 might be associated with reactivation of the occipital cortex, due to top-down re-entrant feedback from higher-level visual areas back to the early visual cortex. 53 , 54 Consistent with these studies, our study further suggested that 30-degree defects recruited a top-down modulation to re-activate the residual information inputs to enhance visual representations. Thus, visual attention might enhance visual representations via top-down feedback mechanisms, especially in high-level defects with limited visual inputs.…”
Section: Discussionsupporting
confidence: 86%